IMPORTANCE OF EDUCATION AND SKILLS ON PERFORMANCE OF INSURANCE SECTOR - Kajwang , Ben (Journal of Strategic Management, 2022)
Purpose: The main indicators for performance measurement in the insurance companies are employee satisfaction, employee training time growth rate, employee reasonable proposal growth rate and the number of products developed. As the insurance sector experiences drastic technological changes, the employability skills and academic qualifications required for hiring and retaining employees have also changed. The goal of this study to discuss the importance of education and skills on performance of insurance sector. The purpose of this work is to enhance the reader's understanding on the various ways that HR managers employ to improve the skills of their employees which contributes to the overall performance. Methodology: A desktop literature review was used for this purpose. Relevant seminal references and journal articles for the study were identified using Google Scholar. The inclusion criteria entailed papers that were not over five years old. Results: From the findings, researchers have advocated for insurance companies to engage their employees on continuous trainings and systematic development of skills that contribute to improved welfare of their employees and increased organizational productivity and profitability. It is therefore necessary that HR managers invest in human resource practices such as trainings and rewards, personnel development, in order to enhance productivity and the overall performance of the organization. Recommendations: The study recommended that consistent trainings and systematic development of skills should be provided in all the levels of the insurance sector. In addition, insurance sector should train their employees on the use of system software such as ERP system that enables employees carry out their tasks faster and efficiently and as a result contribute to the overall performance.